Assessment and comparative study of diosgenin doses in alleviating experimental periodontitis - Alper Kızıldağ; Aysan Lektemür Alpan; Tuğba Köseoğlu Aydın; Melih Özdede; Özlem Özmen (BMC, 2024)
Abstract Background This study was performed to determine the therapeutic effects of diosgenin (DG) which is a steroidal saponin, administered at different doses on alveolar bone loss (ABL) in rats with experimental periodontitis using immunohistochemical and cone-beam computed tomography (CBCT). Methods Thirty-two male Wistar rats divided into four equal groups: control (non-ligated), periodontitis (P), DG-48, and DG-96. Sutures were placed at the gingival margin of the lower first molars to induce experimental periodontitis. Then, 48 and 96 mg/kg of DG was administered to the study groups by oral gavage for 29 days. At day 30, the animals were sacrificed and ABL was determined via CBCT. The expression patterns of osteocalcin (OCN), alkaline phosphatase (ALP), type I collagen (Col-1), B cell lymphoma 2 (Bcl 2), Bcl 2-associated X protein (Bax), bone morphogenetic protein 2 (BMP-2), and receptor activator of NF κB ligand (RANKL) were examined immunohistochemically. Results Histopathologic examination showed all features of the advanced lesion in the P group. DG use decreased all these pathologic changes. It was observed that periodontitis pathology decreased as the dose increased. DG treatment increased the ALP, OCN, Bcl 2, Col-1, and BMP-2 levels in a dose-dependent manner, compared with the P group (p < 0.05). DG decreased the expression of RANKL and Bax in a dose-dependent manner (p < 0.05). ABL was significantly lower in the DG-48 and DG-96 groups than in the P group (p < 0.05). Conclusion Collectively, our findings suggest that DG administration protects rats from periodontal tissue damage with a dose-dependent manner, provides an increase in markers of bone formation, decreases in Bax/Bcl-2 ratio and osteoclast activation.